EXPERT SYSTEM MODEL FOR ASSISTANCE TO MANAGEMENT IN CHOOSING OPTIMAL WEB HOSTING - Трајковић, Славиша; Дашић, Милош; Делетић, Милан (Economic Outlook, 2022)
The paper discusses the model of a software solution in the form of an expert system that helps entrepreneurs and companies in choosing web hosting and service packages for the distribution of their web applications. The software, based on the parameters entered by the user, analyzes 10 factors that are important when deciding on the choice of hosting, and based on the answers received by the user recommends one of the alternatives that best suits his preferences and capabilities. The model of the expert system has an advisory character in making decisions on the choice of adequate hosting and can be upgraded by introducing new parameters, rules and conclusions as proposed solutions, to include new problem situations. The aim of this paper is to point out the possibility of creating artificial intelligence systems that can help in making adequate business decisions for the electronic market.
Keywords: expert systems; artificial intelligence; e-business; choice of web hosting